Online Interactions: An Exploration of Migrant Experiences With Government Surveillance From Home Nations - Mohamed, Amina (Auckland University of Technology, 2021)
The research aims to get a better understanding of the experiences of migrants in their pursuit to maintain relationship with their connections back home and how their practices limit surveillance by the governments of those countries. The practice theory theoretical framework was used to address the research objective and to observe their practices. This is a small-scale qualitative study which uses the interpretive descriptive methodology to explore the experiences of migrants living in New Zealand their online interactions. New Zealand is a diverse country with a large migrant population that will continue to grow. However, far too little attention has been paid to their group and their online interactions. This research aims to contribute to the limited literature on the topics and to use the knowledge to identify ways to better integrate migrants within New Zealand society.
Keywords: Government; Migrants; Online; Social media; Surveillance